2020
DOI: 10.1038/s41598-020-72389-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlated chromosomal periodicities according to the growth rate and gene expression

Abstract: Linking genetic information to population fitness is crucial to understanding living organisms. Despite the abundant knowledge of the genetic contribution to growth, the overall patterns/features connecting genes, their expression, and growth remain unclear. To reveal the quantitative and direct connections, systematic growth assays of single-gene knockout Escherichia coli strains under both rich and poor nutritional conditions were performed; subsequently, the resultant growth rates were associated with the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…The temporal OD 600 reads were exported from the plate reader and processed with Python. The growth parameters r and K were evaluated according to previous reports [30, 46] using a previously developed Python program [30]. In brief, r was defined as the mean of three continuous logarithmic slopes of every two neighboring OD 600 values within the exponential growth phase using “gradient” in the “NumPy” library.…”
Section: Methodsmentioning
confidence: 99%
“…The temporal OD 600 reads were exported from the plate reader and processed with Python. The growth parameters r and K were evaluated according to previous reports [30, 46] using a previously developed Python program [30]. In brief, r was defined as the mean of three continuous logarithmic slopes of every two neighboring OD 600 values within the exponential growth phase using “gradient” in the “NumPy” library.…”
Section: Methodsmentioning
confidence: 99%
“…As the differentiation in decision-making components allowed the independent decision for varied growth phases, the previously reported correlated changes in the growth parameters 27, 28, 29, 30, 31 were supposed to be weakened. However, the three parameters remained significantly correlated (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8B). The relative expression level of each gene (protein) was calculated as the mean of biologically repeated transcripts, according to previous reports 30, 53 . The results showed that the relative abundances of intracellular Ile and BCAAs were significantly higher than their theoretical ratios, i.e., one or three out of 20 amino acids, 5 or 15%, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in growth media was representative of environmental diversity. Media variation could intuitively disturb the growth rates, as experimentally demonstrated with the wild-type ( Aida et al, 2022 ), single-gene knockout ( Liu et al, 2020 ), genome-reduced ( Kurokawa et al, 2016 ), and laboratory-evolved strains ( Kurokawa et al, 2022 ). The changes in growth media also adjusted the mutation rates of the wild-type and genome-reduced strains ( Nishimura et al, 2017 ) and those of MMR deficient strains ( Ishizawa et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%